2013
DOI: 10.1021/ja4095473
|View full text |Cite
|
Sign up to set email alerts
|

Brønsted Acid Catalyzed Enantioselective Indole Aza-Claisen Rearrangement Mediated by an Arene CH–O Interaction

Abstract: Although the aromatic aza-Claisen rearrangement is a general strategy for accessing substituted aromatic amines, there are no highly enantioselective examples of this process. We report the first Brønsted acid catalyzed enantioselective indole aza-Claisen rearrangement for the synthesis of chiral 3-amino-2-substituted indoles. We present evidence for an arene CH-O interaction as a source of activation and stereoinduction, which is an unprecedented phenomenon in enantioselective Brønsted acid catalysis. The pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
32
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(36 citation statements)
references
References 86 publications
4
32
0
Order By: Relevance
“…For instance, in TS major for 6 (see Figure 5a)t here is as tabilizingC H···O interaction between the methoxy group and the carbonyl oxygen of the catalyst. [108][109][110][111][112] Similar interactions are presenti nT S major for the other substrates. In the minor TS, on the other hand, the oxygen of this methoxy group is positioned over acetic acid, which presumably destabilizes TS minor .…”
Section: Resultssupporting
confidence: 53%
See 1 more Smart Citation
“…For instance, in TS major for 6 (see Figure 5a)t here is as tabilizingC H···O interaction between the methoxy group and the carbonyl oxygen of the catalyst. [108][109][110][111][112] Similar interactions are presenti nT S major for the other substrates. In the minor TS, on the other hand, the oxygen of this methoxy group is positioned over acetic acid, which presumably destabilizes TS minor .…”
Section: Resultssupporting
confidence: 53%
“…Instead, the substituents engage in other non‐covalent interactions with the catalyst. For instance, in TS major for 6 (see Figure a) there is a stabilizing CH⋅⋅⋅O interaction between the methoxy group and the carbonyl oxygen of the catalyst . Similar interactions are present in TS major for the other substrates.…”
Section: Resultsmentioning
confidence: 99%
“…However, the enantioselective versions are still in great demand and no highly enantioselective examples of this process have been reported . Tantillo, Tambar and co‐workers realized in 2013 a chiral phosphoric acid catalyzed enantioselective indole aza‐Claisen rearrangement of N ‐allyl‐3‐aminoindoles 57 . A series of 3‐amino‐2‐substituted indoles 58 were obtained in high yields with excellent enantioselectivities (Scheme ).…”
Section: Enantioselective [33]‐sigmatropic Rearrangementsmentioning
confidence: 99%
“…[11] Several asymmetric indole C2-allylation procedures have been developed following this approach. [12] However,t hese strategies almost always lead to the formation of annulated C2-allylated indoles.Asearch of the literature revealed that the sole exception to this generalization comes from Tambar et al [13] who developed an innovative intramolecular route to branched, highly enantioenriched C2-allylated 3-amino indoles employing an enantioselective aza-Claisen rearrangement (Scheme 1, c).…”
Section: Introductionmentioning
confidence: 99%